Design and Modeling of On-Chip Planar Capacitor for Radio Frequency Application - Mohd. Noor, Mariyatul Qibthiyah; Esa, Mazlina (School of Postgraduate Studies, UTM, 2006)
The on-chip RF capacitor is one of the key components for RF integrated circuit designs such as filters and oscillators. This paper presents the investigations performed on the design of an interdigital capacitor configuration for RFICs. Geometry design variables include number of finger, finger length, finger width, finger gap, end gap, terminal width, strip thickness, substrate height, metal types and dielectric constant. Quality factor is the essential parameter as it is an index for the efficiency of a capacitor's performance. The physical model of an interdigital capacitor is first determined. Then, its equivalent lumped circuit is simulated. The effects of parameter variations on quality factor and capacitance value are discussed and shown. An optimised interdigital capacitor can be obtained through their performances.